Pengaruh Teori Berlakunya Hukum Islam Terhadap Pelaksanaan Peradilan Agama Di Indonesia - Edi Gunawan (Jurnal Ilmiah Al-Syir'ah, 2017)
The theories of Islamic law provide a very big influence on the implementation of religious courts in Indonesia. This influence began to take place in the era of reception in complexion, by enacting full Islamic law against Muslims, as a consequence of the belief of embracing Islam. After the independence of Indonesia, Islamic law began to apply nationally, it is evidenced by the recognition and establishment of a judicial institution that specifically handles matters relating to Islamic law as stipulated in Law no. 48 of 2009 on Judicial Power and Law no. 50 of 2009 on Religious Courts. Therefore, there is a wide range of opportunities for the Islamic legal system to enrich the treasures of Islamic legal traditions in Indonesia through the reform and establishment of new laws based on Islamic law applicable in national law.